Clinical performance of intramedullary nailing system for tibia fractures: a retrospective study - Mishra, Shashank; Kumar, Mohit; Kumar, Prashant; Luthra, Gaurav (International Journal of Research in Orthopaedics, 2021)
Background: In this study, we aimed to investigate the performance of the intramedullary tibia nailing system while treating the tibia fracture fixation. Methods: In this retrospective study, studied the results of intramedullary tibia nail in treatment of tibia fracture. A total of 25 consecutive patients were included in this study (11 male, 14 female and average age 42.9 years). Fracture type was classified as per the Muller AO classification of fracture. Results: The outcomes of clinical treatment were obtained in our study; no pain (92%), mild pain (8%) after 2 year follow up. The follow up of patients were taken on 1 month, 6 months, 1 year and 2 years according to visual analog scale (VAS) score. Paired t test was performed for statistical data analysis using minitab and values of p<0.05 were taken to indicate significant value with confidence interval of 95%. No implant related problem have been found like loosening, bending and corrosion. Conclusions: Our outcomes with interlocking cannulated and expert tibial interlocking nailing are empowering and exhibit the advantages of new nailing framework. It has been concluded that intramedullary tibia nailing system is best method for treatment of tibia fracture with good results and outcomes.